(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the interpretation of the theme of the Afghan War in Uzbek and world literature and the artistic analysis of Abdugafur Iskandar’s memoir-essay "Afghan tola fig’onim". The work highlights the impact of war on the human psyche, the image of the mother, the motif of the letter, the phenomenon of fear, and internal suffering. The author interprets the war not as glory, but as a human tragedy. The study reveals the ideological and artistic features of the work and justifies its promotion of the idea of ​​​​glorifying peace and preserving humanity.